CURVATURE DUCTILITYOF REINFORCED CONCRETE BEAM SECTIONS STIFFENED WITH STEEL PLATES (Journal of Engineering, 2006)
This paper presents theoretical parametric study of the curvature ductility capacity forreinforced concrete beam sections stiffened with steel plates. The study considers the behavior ofconcrete and reinforcing steel under different strain rates. A computer program has been written tocompute the curvature ductility taking into account the spalling in concrete cover. Strain ratesensitive constitutive models of steel and concrete were used for predicting the moment-curvaturerelationship of reinforced concrete beams at different rate of straining. The study parameters are theyield strength of main reinforcement, yield strength of transverse reinforcement, compressivestrength of concrete, spacing of stirrups and steel plate thickness. The results indicated that higherstrain rates improve both the curvature ductility and the moment capacity of reinforced concretebeam sections. Moreover the section curvature ductility increases as the thickness of the stiffeningplates decreases.